Plan estratégico para incrementar la demanda en los Posgrados de la Facultad de Ciencias Agropecuarias, Universidad Nacional de Colombia sede Palmira. (2020)
This work analyzes the factors that influence the demand for graduate programs of the Faculty of Agricultural Sciences, and identifies the level of satisfaction of the university community with the academic quality, the physical spaces and the national and international projection of the Palmira Campus. The study develops an analysis of the motivations that students have to carry out postgraduate studies at the Palmira campus, and identifies the economic and social threats that both the students and the programs themselves have to continue their legacy. The economic and social conditions of the students and the trends of the graduate programs of the Faculty of Agricultural Sciences must be aligned to achieve both academic benefits for Headquarters, contributing to the development of the region.